2016
DOI: 10.1016/j.bone.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The roles of vascular endothelial growth factor in bone repair and regeneration

Abstract: Vascular endothelial growth factor-A (VEGF) is one of the most important growth factors for regulation of vascular development and angiogenesis. Since bone is a highly vascularized organ and angiogenesis plays an important role in osteogenesis, VEGF also influences skeletal development and postnatal bone repair. Compromised bone repair and regeneration in many patients can be attributed to impaired blood supply; thus, modulation of VEGF levels in bones represents a potential strategy for treating compromised b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
359
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 477 publications
(380 citation statements)
references
References 136 publications
14
359
0
7
Order By: Relevance
“…In bone tissue, TGF-β, which is stored in the matrix and is released during bone resorption by osteoclasts, is generally recognized to promote bone remodeling process [21]. On the other hand, it is widely accepted that VEGF plays an important role as an angiogenic factor in the bone remodeling and the repair [19]. It has been reported that microRNA-10a plays suppressive roles in the differentiation of osteoblast-like MC3T3-E1 cells and pro-angiogenic activity including VEGF synthesis of umbilical vein endothelial cells, representing a novel potential therapeutic target for bone regeneration-related diseases [50].…”
Section: Discussionmentioning
confidence: 99%
“…In bone tissue, TGF-β, which is stored in the matrix and is released during bone resorption by osteoclasts, is generally recognized to promote bone remodeling process [21]. On the other hand, it is widely accepted that VEGF plays an important role as an angiogenic factor in the bone remodeling and the repair [19]. It has been reported that microRNA-10a plays suppressive roles in the differentiation of osteoblast-like MC3T3-E1 cells and pro-angiogenic activity including VEGF synthesis of umbilical vein endothelial cells, representing a novel potential therapeutic target for bone regeneration-related diseases [50].…”
Section: Discussionmentioning
confidence: 99%
“…Helmrich et al 54) stressed in his work that in minimizing cell expansion, the osteogenic differentiation potential of bone marrow-MSCs was maintained, but a strong reduction in bone formation was observed when the VEGF gene over-expressed. VEGF has been reported to participate in several stages of bone repair and regeneration; however, most studies have primarily examined the consequences for bone repair when VEGF levels were manipulated at local injury sites or systemically 55) . Using a free dose of the VEGF may recruit excess numbers of osteoclasts, resulting in resorption of newly formed bone, since VEGF regulates the diff erentiation and migration of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike endochondral ossification, where blood vessels prevent the formation of cartilage, intramembranous bone formation relies on the coupling of angiogenesis and osteogenesis. VEGF has an essential role in this coupling since both vascular and skeletal morphogenesis is VEGF dependent 28,29) . Bone formation is a complex developmental process involving the diff erentiation of mesenchymal stem cells to osteoblasts 28) .…”
Section: Introductionmentioning
confidence: 99%
“…Since angiogenesis influences osteogenesis, VEGF is important in bone formation and remodelling [163]. Recognizing that the vascularization and osteogenesis of block grafts still remains a key problem for dentists, Du et al [46][47] attempted to promote angiogenesis and prevascularization by seeding nano-HA (nHA)/coral blocks with angiogenic recombinant human vascular endothelial growth factor165 (rhVEGF165).…”
Section: Coral-derived Bone Grafts Substitutesmentioning
confidence: 99%